PENGEMBANGAN DESA WISATA DI DESA BONGKASA KECAMATAN ABIANSEMAL KABUPATEN BADUNG PROVINSI BALI - I.G.A.O. Mahagangga; M. Sukana; I.B. Suryawan; I.P. Anom (Buletin Udayana Mengabdi, 2018)
The main problem is how to start the development of tourist village in Bongkasa village. In fact, the locationof this village near Ubud (Gianyar) that many tourists visited everyday. The purpose of are to provide anunderstanding of the potential of tourism owned and provide tourism planning as grand design to develop thevillage of Bongkasa as a tourist village. The scope are potential tourism analysis and tourism planning.Tourism planning based on the potential and existing conditions. The method used are counseling and FGD.Starting from the initial survey, field research and literature study. The results are synergized with theaspirations of local society and analyzed qualitatively from science of tourism perspective. Revealed that thevillage of Bongkasa very feasible for the development of tourist villages with potential of nature, culturalpotential and artificial potential. Bongkasa as a tourist village need macro planning as a grand design calledframework implementation policy development model.